Educación financiera y su influencia en el proceso de enseñanza y aprendizaje de las matemáticas de los estudiantes de bachillerato de la unidad educativa Municipal de Quevedo en el periodo lectivo 2023-2024 - Vásquez Zambrano, Heidy Madelyn (2024)
Currently, financial education has become an essential competence for adult life, however, its integration into educational systems is often fragmented or insufficient. This deficit manifests itself in low financial understanding among young people. This is why the objective of this research work is to evaluate the influence of financial education on the teaching and learning process of mathematics in high school students of the Municipal Educational Unit of Quevedo during the 2023/2024 school year. The need to address this issue arises from the perception that the lack of connection between financial education and mathematics learning can be limiting. The selected methodology is a mixed approach, combining qualitative and quantitative elements. The interview with an authority and the survey with the mathematics teachers of the institution were applied as data collection instruments, in order to obtain detailed perceptions of the institutional reality, in addition, an exhaustive review of the academic literature to theoretically support the proposal to integrate financial education into the mathematics curriculum. This development project identified key factors affecting the relationship between financial education and mathematics learning, and developed a detailed proposal to integrate financial education into the curriculum, with the purpose of improving educational quality and financial skills. of students, preparing them to make informed decisions and face economic challenges.